Osteosarcopenia in metabolic dysfunction–associated steatotic liver disease: from mechanisms to management - Fan, Aili; Zhang, Jie; Ye, Qing (Frontiers in Endocrinology, 2025)
Osteosarcopenia, the coexistence of osteoporosis and sarcopenia, is an emerging and underrecognized complication in patients with metabolic dysfunction-associated steatotic liver disease (MASLD). While muscle and bone loss have been individually observed in MASLD, their combined impact remains poorly addressed in clinical practice. This review outlines the epidemiology, pathophysiological mechanisms, clinical relevance, and current strategies for diagnosing and managing osteosarcopenia in MASLD. Shared pathogenic pathways, including insulin resistance, chronic inflammation, hormonal imbalance, and gut dysbiosis, create a vicious cycle contributing to musculoskeletal degradation and liver disease progression. We highlight the need for proactive screening of osteosarcopenia, and using standardized assessment tools. A multidimensional therapeutic approach, encompassing nutrition, exercise, pharmacotherapy, and emerging metabolic and gut-targeted interventions, may improve not only musculoskeletal health but also hepatic and systemic outcomes. Future studies are warranted to improve long-term prognosis for both osteosarcopenia and MASLD.